Recipient bed perfusion as a predictor for postoperative complications in irradiated patients with microvascular free tissue transfer of the head and neck area: a clinical analysis of 191 microvascular free flaps - Foerster, Yannick; Baumann, Laura; Kafantari, Ino; Olmos, Manuel; Wehrhan, Falk; Kesting, Marco Rainer; Preidl, Raimund (Oral and maxillofacial surgery, 2022)
Purpose Despite microvascular free tissue transfer being the mainstay of care in the reconstruction of larger maxillofacial defects, a significant number of patients experience postoperative complications due to impaired blood supply of the flap. In this context, the early influence of recipient bed perfusion remains unclear, but there is evidence that it is associated with free flap viability immediately after surgery. Methods We analyzed flap and recipient bed perfusion within the first 2 weeks after surgery by using the oxygen-to-see device. One hundred ninety-one patients who underwent free flap surgery in our department were included. Results Flow parameters were higher and postoperative complications were less frequent in radial forearm free flaps compared to any other type of flap. Flow parameters of the recipient bed were higher than transferred tissue at all times, implicating flap autonomization is not completed within 2 weeks. Previous radiotherapy significantly decreased flow parameters of the recipient bed but not of the flaps. Furthermore, irradiated patients with postoperative complications were found to have reduced flow parameters of their recipient bed compared to non-irradiated patients with postoperative complications. Conclusion We conclude that monitoring of recipient bed perfusion is useful for detecting flap compromise of irradiated patients in the early postoperative period.
CRIS-Team WoS Importer:2022-05-27
Keywords: Microvascular free flap; Oxygen-to-see; Recipient bed; Radiotherapy; Monitoring; Complications